2017
DOI: 10.1093/jxb/erx077
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Formation 1, a plant-conserved gene, encodes an OmpH/coiled-coil motif-containing protein required for meiotic recombination in rice

Abstract: Highlight OsBVF1 is a novel gene that is required for meiotic recombination in the monocot rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…Recently, OsP31 comet (OsBVF1) was identified as a CRC1-interacting protein that has similarity to the human mitotic arrest-deficient 2 (Mad2) binding protein. It was demonstrated to be an SC component, and it participates in meiotic DSB formation (105,252). These results suggest that the SC is important for both DSB formation and subsequent recombination.…”
Section: Double-strand Break Formationmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, OsP31 comet (OsBVF1) was identified as a CRC1-interacting protein that has similarity to the human mitotic arrest-deficient 2 (Mad2) binding protein. It was demonstrated to be an SC component, and it participates in meiotic DSB formation (105,252). These results suggest that the SC is important for both DSB formation and subsequent recombination.…”
Section: Double-strand Break Formationmentioning
confidence: 90%
“…In S. cerevisiae, in addition to the SPO11 complex, there are at least nine other Spo11-or DSB-associated proteins, including Mre11, Rad50, Xrs2, Ski8, Rec102, Rec104, Rec114, Mei4, and Mer2 (157), which form different subcomplexes to promote Spo11-dependent DSB formation. There are also DSB-associated proteins in plants, including those that are plant specific or have diverged substantially, such as AtPRD1, AtPRD2, AtPRD3, AtDFO, OsCRC1, OsSDS, and OsP31 comet (OsBVF1) (58,105,150,163,235,248,252). Among these, AtPRD1 and At-PRD2 are likely the mouse homologs of, respectively, MEI1 and MEI4 (58,59), and AtPRD3, OsPAIR1, and AtDFO (DSB FORMATION) are likely plant-specific proteins (58,163,248).…”
Section: Double-strand Break Formationmentioning
confidence: 99%
“…We identified a new male-sterile mutant from our rice mutant library (generated by 60 Co γ-ray irradiation of the japonica cultivar 02428; Ji et al , 2013 ; Niu et al , 2013 ; Zhou et al , 2017 ). We named this mutant oslecrk5 because subsequent analysis showed that its sterility is caused by a mutation in the rice LecRLK gene OsLecRK5 (see below).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade many homologous recombination-related genes have been identified, but their potential for hybrid rice breeding has never been harvested. For example, the PAIR2 , PAIR3 , BVF1 , and SPO11 are essential for chromosome recombination, and the mutations cause complete male sterility ( Nonomura et al, 2004 ; Yuan et al, 2009 ; Yu et al, 2010 ; Zhou et al, 2017 ). Interestingly, their mutants produce intact univalent, hence perfectly useful.…”
Section: Biotechnological Strategies To Develop Male Sterility and Hymentioning
confidence: 99%